2021
DOI: 10.21744/lingcure.v5ns3.1365
|View full text |Cite
|
Sign up to set email alerts
|

study on impact of PSL on gross NPAS of nationalised banks: an empirical approach

Abstract: In order to encourage banks to lend more to neglected areas of the economy, the idea of a priority sector was introduced. These priority sectors add significantly to gross domestic product but have not received sufficient finance to function adequately. However, lending in the priority sector is not very warmly welcomed by the banks, particularly nationalized banks in India, as they generate more nonperforming assets than other sectors. It is the priority sector that contributes to the biggest default.  As far… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Gaur and Mohapatra (2020) the repercussions of NPA provided by various private and public sector banks to various priority sectors for the period 2012–2017 and revealed that lending to priority sectors boosts GDP while having no effect on the NPA ratio. By using panel data analysis, Susena et al (2021) found that PSL and GDP have a positive link and a causal relationship that goes both ways. Using panel least square regression and ICICI Bank data over a 10-year period, Desai (2021) compares the sub-sectors within the priority sector and concludes that bank profitability is significantly impacted negatively by agriculture finance, whereas lending to other sectors and personal credit have no discernible influence.…”
Section: Review Of Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…Gaur and Mohapatra (2020) the repercussions of NPA provided by various private and public sector banks to various priority sectors for the period 2012–2017 and revealed that lending to priority sectors boosts GDP while having no effect on the NPA ratio. By using panel data analysis, Susena et al (2021) found that PSL and GDP have a positive link and a causal relationship that goes both ways. Using panel least square regression and ICICI Bank data over a 10-year period, Desai (2021) compares the sub-sectors within the priority sector and concludes that bank profitability is significantly impacted negatively by agriculture finance, whereas lending to other sectors and personal credit have no discernible influence.…”
Section: Review Of Literaturementioning
confidence: 99%
“…To promote holistic development, the Central Bank of India (RBI) has identified banks as priority sector lenders, rather than concentrating only on the financial sector (Nagarajan, Sathyanarayana, and Ali, 2013). The term “priority sector” refers to industries that contribute the most to gross domestic production (GDP) but receive the least financial assistance (Susena et al , 2021; Singh et al , 2023). Priority sector lending’s (PSL) fundamental objective is to offer ignored sections of society sufficient and prompt finance at reasonable interest rates (Savitha and Kumar, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation